CIRCLE OF LIFE HIV/AIDS-PREVENTION INTERVENTION FOR AMERICAN INDIAN AND ALASKA NATIVE YOUTH - Kaufman, Carol E. (Am Indian Alsk Native Ment Health Res, 2012)
This article describes the objectives, theoretical bases, development process, and evaluation efforts to-date for the Circle of Life (COL) curricula, HIV/AIDS prevention interventions designed for American Indian and Alaska Native (AI/AN) youth. The curricula are based on Indigenous models of learning and behavior encompassing concepts of Western theories of health behavior change. The curricula underwent extensive national and community review. Subsequent advances include the development of a computer-based version of the intervention.